Scaling nonhierarchically: A theory of conflict‐free organizational growth with limited hierarchical growth - Lee, Eucman; Ilseven, Ekin; Puranam, Phanish (Strategic Management Journal, 2023)
Research Summary We propose a theory that explains variations in the relationship between an organization's size and the extent of its authority hierarchy (as captured in managerial intensity). Conceptualizing authority hierarchy as a means to manage conflicts among subordinates, we formulate a model in which the number of managers required depends on the magnitude of conflicts generated between and within groups of workers. Our analysis shows that scaling non‐hierarchically can be accomplished either by creating low conflict “self‐managing” teams or reducing conflicts between many “self‐contained” teams, but which path is more effective varies by situation. Small initial differences in terms of their emphasis on within vs. between team conflict mitigation can lead to large differences as firms scale over time in the extent of their authority hierarchies. Managerial Summary Managing without an extensive hierarchy can be attractive for a variety of reasons, but under what conditions is it possible in large scale organizations? We build on the premise that the managerial hierarchy of authority serves to resolve conflicts that employees cannot resolve peer‐to‐peer (i.e., there are limits to scaling groups that manage themselves consensually). We develop a formal theory that predicts that there are three levers that can slow down the growth of managerial hierarchy even as the organization scales: investing in the technology and culture needed to (a) expand managerial capacity particularly toward the apex of the hierarchy (b) create “self‐managed” teams that produce few conflicts in need of managerial resolution and (c) create “self‐contained” teams that generate few conflicts between them that need escalation up the hierarchy for resolution. The third is likely to be the most effective lever as organizations grow.